Strategi Kampanye Yayasan Pejuang Tangguh Dalam Membangun Citra Organisasi Melalui Program “Dengan TPT Cegah TBC” - Putri Marshada Lestari; Syifa Astasia Utari (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
A campaign is a public relations activity that can be a strategy in building a positive organizational image. This is because the campaign allows the organization to convey messages according to public needs, including the issue of Tuberculosis which is currently a challenge in Indonesia due to a lack of education. Therefore, the Pejuang Tangguh Foundation (PETA) runs the "Dengan TPT Cegah TBC" program which not only encourages changes in public attitudes but also serves as a means to build the organization's image. This study aims to determine the "Dengan TPT Cegah TBC" campaign strategy by the Pejuang Tangguh Foundation and the organization's image through the campaign. The theory in this study is based on the public relations campaign theory by Anne Gregory (2018) and the image formation theory by John S. Nimpoeno (2020). The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of this study indicate that PETA carries out a campaign strategy that includes ten dimensions: analysis, objectives, public, messages, strategies, tactics, timescale, resources, evaluation and review. Through the campaign strategy, the organization can build an image by shaping public perceptions, cognition, attitudes, and motivation. Thus, the program not only runs effectively, but also plays a role in building a positive image of the organization.